2020
DOI: 10.3389/fimmu.2020.00536
|View full text |Cite
|
Sign up to set email alerts
|

RIPK3 and Caspase-1/11 Are Necessary for Optimal Antigen-Specific CD8 T Cell Response Elicited by Genetically Modified Listeria monocytogenes

Abstract: Efficient induction of effector and long-term protective antigen-specific CD8 + T memory response by vaccination is essential to eliminate malignant and pathogen-infected cells. Intracellular infectious bacteria, including Listeria monocytogenes, have been considered potent vectors to carry multiple therapeutic proteins and generate antigenspecific CD8 + T cell responses. Although the role of molecules involved in inflammatory cell death pathways, such as necroptosis (RIPK3-mediated) and pyroptosis (Caspase-1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Necroptosis is a programed cell death response that is mediated by the RIPK3/RIPK1 signaling complex ( Pasparakis and Vandenabeele, 2015 ), and in certain contexts is initiated by IFN-STAT1 signaling ( Thapa et al., 2013 ). Several studies have demonstrated that RIPK3-dependent necroptosis is potent at inducing CD8 T cell activation in vitro and in vivo ( Yatim et al., 2015 ; Ren et al., 2017 ; Rana et al., 2020 ; Aaes and Vandenabeele, 2021 ). Hence the role of RIPK3 was explored.…”
Section: Resultsmentioning
confidence: 99%
“…Necroptosis is a programed cell death response that is mediated by the RIPK3/RIPK1 signaling complex ( Pasparakis and Vandenabeele, 2015 ), and in certain contexts is initiated by IFN-STAT1 signaling ( Thapa et al., 2013 ). Several studies have demonstrated that RIPK3-dependent necroptosis is potent at inducing CD8 T cell activation in vitro and in vivo ( Yatim et al., 2015 ; Ren et al., 2017 ; Rana et al., 2020 ; Aaes and Vandenabeele, 2021 ). Hence the role of RIPK3 was explored.…”
Section: Resultsmentioning
confidence: 99%
“…Our results contrast with Rana et. al (2020) who observed that Caspase-1 was necessary for optimal T-cell responses to L. monocytogenes 34 . Our strain is deficient for the host-actin assembly protein ActA to attenuate its virulence and is cleared in 2-3 days 20 while Rana et al (2020) utilized WT L. monocytogenes which persisted for nearly 7 days-post immunization and is not suitable as a vaccine strain.…”
Section: Discussionmentioning
confidence: 99%
“…IL-18 influences the activation of CD4 + T lymphocytes, resulting in the secretion of IFN-γ and the clearance of S. Typhimurium infection from the spleen of mice in a MHC-II-independent manner . CD8 + T lymphocytes are essential in clearing the infection caused by cytosolic bacteria such as Listeria monocytogenes . , However, the same is unknown during the infection of vacuolar pathogens such as S. Typhimurium. , The successful onset of typhoid fever in humans by S. Typhi depends on its ability to evade and eventually establish an intracellular proliferating niche in phagocytes. In the following part of this Review, we discuss the intelligent approaches employed by S. Typhi and S. Typhimurium to deceive the immune system and initiate systemic infections in humans and mice.…”
Section: Virulence Determinants Of Salmonella Pathogenesismentioning
confidence: 99%
“… 197 CD8 + T lymphocytes are essential in clearing the infection caused by cytosolic bacteria such as Listeria monocytogenes . 198 , 199 However, the same is unknown during the infection of vacuolar pathogens such as S. Typhimurium. 200 , 201 The successful onset of typhoid fever in humans by S. Typhi depends on its ability to evade and eventually establish an intracellular proliferating niche in phagocytes.…”
Section: Virulence Determinants Of Salmonella Path...mentioning
confidence: 99%